Analysis of the professional area of nutrition in multidisciplinary residency programs in collective health in northeastern Brazil (Research, Society and Development, 2023)
Objective: To analyze the access and supply of places in the area of nutrition in the Multiprofessional Residency Programs in Collective Health (PRMSC) located in the northeast of Brazil. Methodology: This is a descriptive and documentary study, in which data was collected on the PRMSC located in northeastern Brazil between July and October 2023. Information was extracted on the number of PRMSC per state of the federation; the number of places on offer; the professional categories covered; the type of institution proposing them and the municipalities where they are located. Results: A total of 14 PRMSC were identified, distributed over 04 states, offering 680 places. Of these, only 11 PRMSC offer 55 places in the area of nutrition, which represents 8.6% of the total. The number of places on offer is concentrated in Pernambuco (83.5%); Bahia (8.5%); Ceará (6.2%); and Paraíba (1.8%). The nature of the proposing institutions is characterized by health and higher education institutions located in the municipalities of Crato (Ceará); Salvador (Bahia); Afogados de Ingazeira, Arcoverde, Caruaru, Garanhuns, Goiana, Ouricuri, Recife, Salgueiro and Serra Talhada (Pernambuco); Catolé do Rocha and Sousa (Paraíba). Conclusion: In general, it can be seen that the northeast region has an important number of vacancies for PRMSC, with the area of nutrition as the second largest professional category offered in the programs, especially in Pernambuco. However, it is necessary to emphasize the importance of expanding the implementation of new PRMSC in other states in order to promote the qualification of professionals in health care networks in the regional context.